Mapping the distribution of the in Nepenthes Malaysia using Geographical Information System (GIS) - MOHD AMRAN, NURMASITAH; Nazirah Mohamad Abdullah,; Nurul Hazirah Nor Hassan,; Noor Azlin Harun,; Nurhidayah Nasir, (Enhanced Knowledge in Sciences and Technology, 2024)
This research endeavors to map the distribution of Nepenthes, carnivorous plants, across the diverse ecosystems of Malaysia, utilizing Geographic Information System (GIS) technology. The study aims to provide comprehensive insights into the spatial occurrence, habitat preferences, and environmental indicators associated with Nepenthes species. Systematic field surveys and remote sensing techniques will be employed to collect spatial and attribute data, generating a detailed map illustrating the distribution patterns. By addressing existing gaps in knowledge, this research seeks to contribute to biodiversity conservation efforts and inform habitat management strategies. The findings are expected to enhance our understanding of Nepenthes ecology and offer valuable insights into the broader field of tropical plant species distributions.